Pengaruh Suhu Perendaman dengan Larutan Natrium Metabisulfit terhadap Karakteristik Fisikokimia Tepung Labu Kuning (Cucurbita moschata D.) - Rina Rismaya; Yesika Kristiani; Elvira Syamsir; Didah Nur Faridah (Food Scientia : Journal of Food Science and Technology, 2022)
Pumpkin (Cucurbita moschata D.) is an agricultural commodity with a fairly complete nutritional content and high fiber. The use of pumpkin which is still limited to traditional processed food can be expanded by processing it into flour. Pumpkin flour has a longer shelf life than a fresh pumpkin. It is also easy to distribute and to process into various types of processed food. This study is aimed to evaluate the physicochemical characteristics of pumpkin flour produced from different pretreatments. Pretreatments such as soaking in 0.10% sodium metabisulfite solution at room temperature 30 ºC and 80ºC for 10 minutes. The parameters measured were moisture content, ash, protein, fat, carbohydrates, dietary fiber, and color. Based on the test results, the difference in immersion temperature only significantly affected the color value. Pumpkin flour soaked in 0,10% sodium metabisulfite at an initial temperature of 80 ºC had color values of L= 64,87 ± 0,04; b* +52,95 ± 0,05, higher but color value a* =+6,89 ± 0,06.